Implementing One Health (OH) Guideline for Effective Cross-Sectoral Collaboration: Enablers and Challenges for Neglected Zoonoses and Emerging Infectious Diseases (EIDs) Control in Kulonprogo District, Yogyakarta Province, Indonesia (Berita Kedokteran Masyarakat (BKM), 2020)
Zoonoses are communicable diseases that transmissible between animals to humans, and vice versa. There are approximately 75% of emerging infectious diseases (EIDs) that originated from the animal. It has been an evidence-based practice for decades that One Health (OH) approach which integrates humans, animals and environmental health could provide earlier windows opportunity for better zoonoses control. We used a qualitative method using document review and semi-structured depth interviews to understand the barriers and enablers for implementing OH guidelines from Coordinating Ministry for Human Development and Cultural Affairs for cross-sectoral collaboration in Kulon Progo district, Yogyakarta Province, Indonesia. Totally, 13 participants were interviewed, who came from different backgrounds and expertise, including animal, public and environmental health, social science, governance, and disaster response. The document review shows precedent of cross-sectoral collaboration between public and animal health on national level that was initiated in 1972. Based on the recent trend of the public health problems in Kulon Progo, there are significantly lingering and/or increasing number of infectious diseases, both from public and animal health. Those diseases are leptospirosis, scabies, and helminthiasis (ancylostomiasis and ascariasis). All of those diseases are zoonotic and the last two are neglected, which included in neglected tropical diseases (NTDs) by WHO. There are enablers that emerge for implementing OH, including strong commitment, political will, program flexibility, good governance, system support, and thinking. The challenges/barriers that emerge including silo mentality, lack of cross-sectoral communication and coordination, conflict of interest, regulation, political will, siloed education, and funding. The necessary feasible intervention at the district level is to formalize a working group and/or committee for outbreak preparedness. Cross-sectoral meeting for joint-program and funding allocation are crucial for better planning, execution, and program evaluation to tackle zoonotic diseases (both NTDs and EIDs).